P09.13 Impact and cost-effectiveness of point-of-care testing for chlamydia: accounting for geographic variation in infection burden and testing rates, health service configuration, and implementation strategy. (13th September 2015) - Dangerfield, CE; Sherrard-Smith, E; Green, N; Harding-Esch, E; Howell-Jones, R; Choi, Y; Lowndes, CM; White, PJ
Abstract : Introduction: Point-of-care tests (PoCTs) for Chlamydia trachomatis potentially improve control by reducing transmission through reduced treatment delay, reduced loss to follow up, and greater convenience for patients leading to increased testing. However, with ~3–5 fold variation in rates of Chlamydia testing and diagnosis across geographic settings in England, in assessing cost-effectiveness the epidemiological context needs to be considered. Methods: We developed a transmission-dynamic model to capture geographic variation in rates of testing and diagnosis using current technology to allow assessment of the impact of implementing PoCTs in different clinical services in different localities. The model incorporates heterogeneity in sexual partner change rates and is stratified by age and sex. It uses behavioural and prevalence data from the Natsal national survey, and Public Health England surveillance data on testing and diagnosis rates. Uncertainty in natural history and behavioural parameters is captured by Monte Carlo methods. Health service reconfiguration using PoCT is considered, including rates of PoCT introduction and reduction in presumptive treatment. Results: The model captures observed geographic variation in rates of testing and diagnosis in females and males, which affects the impact and cost-effectiveness of PoCT introduction. In general, whilst PoCTs may reduce incidence by increasing diagnosis and treatment, if sensitivity is lower than conventional testing then there is potentially increased transmission from false-negative patients. The net effect depends upon characteristics of the particular PoCT. Conclusion: PoCT sensitivity and specificity are key determinants of whether replacing conventional testing is likely to reduce or increase the incidence of infection. Importantly, if the convenience of PoCT increases testing rates then diagnoses might initially increase even though incidence falls; interpretation of surveillance data needs to account for this. This work is the foundation of a user-friendly web-based tool assessing the (cost-) effectiveness of introducing PoCTs in different local settings. Disclosure of interest statement: CED, ESS, NG, EHE, RHJ, YC, CML, and PJW thank Innovate UK for funding. PJW thanks the UK Medical Research Council for Centre funding (grant MR/K010174/1), and also thanks the UK National Institute for Health Research Health Protection Research Unit (NIHR HPRU) in Modelling Methodology at Imperial College London in partnership with Public Health England (PHE) for funding (grant HPRU-2012–10080). The funding sources had no involvement in the study design or conduct; the collection, analysis and interpretation of data; the preparation, review or approval of the manuscript; or the decision to submit the manuscript for publication. The views expressed are those of the authors and not necessarily those of the NHS, the NIHR, the Department of Health, or Public Health England. CED was employed for part of the project by the National Chlamydia Screening Programme. The other authors declare no competing interests.